Two new species of Chionanthus (Oleaceae) from Southern Thailand - Kiew, Ruth; Gardner, Simon; Sidisunthorn, Pindar (Thai Forest Bulletin (Botany), 2016)
Field surveys for the ‘Forest Trees of Southern Thailand’ project resulted in two new Chionanthus species, C. gardneriorum Kiew from Trang Province and C. pyriformis Kiew from Phangnga and Ranong Provinces. The new species are described and illustrated and a key to Chionanthus species in southern Thailand is provided.